2016
DOI: 10.1039/c6gc01394e
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide/dimethyl carbonate: a green system for epoxidation of N-alkylimines and N-sulfonylimines. One-pot synthesis of N-alkyloxaziridines from N-alkylamines and (hetero)aromatic aldehydes

Abstract: A green method for epoxidation of imines using an environmentally benign oxidant system, H2O2/dimethyl carbonate, was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…To prepare the new chiral 1-(arylamino)imidazo[2,1- a ]isoindole-2,5-diones 5a – m under greener conditions, we investigated the reaction in nontoxic solvents such as water and dimethyl carbonate (DMC). Indeed, DMC is well-known as safe reagent and solvent that has been used for many green applications [ 31 33 ]. On the other hand, water is a simply and environmentally benign solvent and interest has increasingly turned to it as the greenest solvent of chemical reactions [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…To prepare the new chiral 1-(arylamino)imidazo[2,1- a ]isoindole-2,5-diones 5a – m under greener conditions, we investigated the reaction in nontoxic solvents such as water and dimethyl carbonate (DMC). Indeed, DMC is well-known as safe reagent and solvent that has been used for many green applications [ 31 33 ]. On the other hand, water is a simply and environmentally benign solvent and interest has increasingly turned to it as the greenest solvent of chemical reactions [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, Ollevier et al reported a novel, green and one-pot synthetic method to derive N-alkyloxaziridines 3 using an eco-friendly oxidant system H 2 O 2 / Dimethylcarbonate (DMC) in 2016. [16] Hydrogen peroxide contain high oxygen content and its byproducts (water and O 2 ) are environment-friendly. Similarly, DMC is a green solvent and reagent due to its high biodegradability and low toxicity.…”
Section: N-alkyl and N-aryloxaziridinesmentioning
confidence: 99%
“…In fact, due to the highest active oxygen content and the formation of water only being a by-product, the use of H 2 O 2 as an oxidant is among the key aspects of modern Green Chemistry nowadays. For example, H 2 O 2 has become the primary oxidant in the selective oxidations of numerous organic substances, such as imines [20], olefins [21][22][23], and alcohols [24].In recent years, the HPPO process based on a TS-1 catalyst, as well as the H 2 O 2 oxidant and methanol solvent, has been industrialized by BASF and Dow, Evonik and Uhde, and Sinopec Changling Refining and Chemical. Nevertheless, the HPPO process still suffers from the use of a methanol solvent.…”
mentioning
confidence: 99%
“…In fact, due to the highest active oxygen content and the formation of water only being a by-product, the use of H 2 O 2 as an oxidant is among the key aspects of modern Green Chemistry nowadays. For example, H 2 O 2 has become the primary oxidant in the selective oxidations of numerous organic substances, such as imines [20], olefins [21][22][23], and alcohols [24].…”
mentioning
confidence: 99%